Evaluating the Reform of Healthcare System in Sicily: variations of efficiency and appropriateness between 2008 and 2010 (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Sicilian government has developed a very ambitious Reform through the Regional Law n. 5 (14th April 2009). Hospitals were requested to ensure the quality of care through monitoring of appropriateness and quality of service. The aim of this study was to assess variations of efficiency and organizational appropriateness of healthcare delivery before and after this Reform and to show patterns associated to different types of healthcare delivery organizations.Methods. This study was based on repeated cross-sectional data for 118 (out of 129) short-term, acute-care, non teaching-and-research Sicilian hospitals, in 2008 and 2010. Congestion and slacks analysis was used, with four inputs, two desirable outputs and two undesirable outputs of healthcare delivery.Results. The loss of desirable output increased between 2008 (23%) and 2010 (31%). Most of the variation between two years in the measured inefficiency could be attributed to congestion due to inappropriate care (p=0.009) and scale inefficiency (p=0.028). Hospitals that have undergone an organizational transformation did not show congestion in the study period. Conversely, hospitals with no variations in their organization were congested in association to the shortfall in the ODs (p=0.019) and in DHs (p=0.018).Conclusion. This study has shown the general worsening of efficiency of acute-care Sicilian hospitals from 2008 and 2010 and, in particular, has suggested that the reduction of efficiency was due to hospitals that have not undergone an organizational transformation. They are medium-low sized and low-complexity public hospitals and for-profits, while larger and high-complexity organizations resulted the least congested ones.